1982
DOI: 10.1002/1097-0142(19820315)49:6<1194::aid-cncr2820490621>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy as an adjuvant in the treatment of carcinoma of the breast

Abstract: During the period from 1950-1974, 510 patients with a diagnosis of invasive ductal carcinoma treated with the standard Halsted radical mastectomy were reviewed retrospectively from the records of the Tumor Clinic of The Memorial Hospital, Danville, Virginia. The primary aim of the study was to determine whether postoperative adjuvant radiation therapy (POART) as delivered in a community hospital setting contributed to better cancer control and effectively influenced five and ten year survival rates. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…39 In 1982, Chu and Kiel compared patients with 4 positive axillary lymph nodes treated with postmastectomy radiation to the chest wall and regional lymph nodes to patients treated with multidrug chemotherapy alone. 40 The radiated patients had a longer time to local recurrence, but no significant difference in disease-free survival.…”
Section: S To 1980smentioning
confidence: 99%
“…39 In 1982, Chu and Kiel compared patients with 4 positive axillary lymph nodes treated with postmastectomy radiation to the chest wall and regional lymph nodes to patients treated with multidrug chemotherapy alone. 40 The radiated patients had a longer time to local recurrence, but no significant difference in disease-free survival.…”
Section: S To 1980smentioning
confidence: 99%
“…The myelosuppressive effect of radiotherapy is known to significantly decrease the maximum chemotherapy dose that can be given (72). Nevin et al (74) showed that postoperative radiotherapy was related with a significant decline in 5-and 10-year survival rates of patients with stage II and III disease with negative nodes. Sternsw~rd (73) reviewed six controlled clinical trials and found survival was decreased from 1-10% in irradiated patients when compared with those treated by mastectomy alone.…”
Section: E Effect Of Adjuvant Chemotherapy On Postmastectomy Recurrementioning
confidence: 99%